1996
DOI: 10.1254/jjp.72.381
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress-Induced Increase in Intracellular Ca2+ and Ca2+-Induced Increase in Oxidative Stress: An Experimental Model Using Dissociated Rat Brain Neurons

Abstract: ABSTRACT-In order to study the oxidative stress-induced change in intracellular concentration of Ca 2+ ([Ca2+];) and Ca2+-induced oxidative stress, effects of hydrogen peroxide and ionomycin, a calcium ionophore, on rat cerebellar neurons were examined using a flow cytometer and fluorescent dyes: fluo-3 for monitoring [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…5B and C). It was previously reported that cellular oxidative stress induced an increase in intracellular Ca 2+ levels [47]. Although the molecular mechanism responsible for the elevation of Ormdl3 expression through FABP4 knockdown is currently unclear, it is possible that the ER stress observed in this study may be secondarily induced by oxidative stress and impaired Ca 2+ homeostasis as a result of FABP4 knockdown.…”
Section: Discussionmentioning
confidence: 58%
“…5B and C). It was previously reported that cellular oxidative stress induced an increase in intracellular Ca 2+ levels [47]. Although the molecular mechanism responsible for the elevation of Ormdl3 expression through FABP4 knockdown is currently unclear, it is possible that the ER stress observed in this study may be secondarily induced by oxidative stress and impaired Ca 2+ homeostasis as a result of FABP4 knockdown.…”
Section: Discussionmentioning
confidence: 58%
“…Various oxidants are known to increase the cytoplasmic free C a 2ϩ concentration, although the exact mechanism for the increase is yet to be established (Suzuki et al, 1997). H 2 O 2 has been shown to increase the intracellular C a 2ϩ level in rat neurons (Oyama et al, 1996). The results presented here indicate that the enhanced C a 2ϩ flux through the neuronal voltagedependent C a 2ϩ channels could contribute to the oxidantinduced increase in the cytosolic C a 2ϩ level.…”
Section: Discussionmentioning
confidence: 61%
“…12,16) Oxidative stress is also induced by abnormally increasing [Ca 2ϩ ]i in neurons. 20,21) Therefore, if EGBL prevents increasing [Ca 2ϩ ]i of neurons by excessive activation of glutamate receptor, it would contribute to the neuroprotective action of EGBL. In this study, EGBL at concentrations of 3 mg/ml or more decreased the increase in [Ca 2ϩ ]i induced by kainate via an activation of non-NMDA receptor (Fig.…”
Section: Discussionmentioning
confidence: 99%